The Interrelationship Between Motor Coordination and Adaptive Behavior in Children With Autism Spectrum Disorder - Bremer, Emily; Cairney, John (Frontiers in Psychology, 2018)
Objective Children with autism spectrum disorder (ASD) experience significant challenges with their motor coordination. It is not, however, well understood how motor coordination may impact the behavioral functioning of children with ASD. Therefore the purpose of this study was to explore the relationships between motor coordination and adaptive behavior in 7-12 year old children with ASD. Methods Motor coordination was assessed using the Movement Assessment Battery for Children, 2nd Edition (MABC-2) and adaptive behavior was assessed by parental report using the Vineland Adaptive Behavior Scales, 2nd Edition (VABS-2) as part of a larger cross-sectional study. Descriptive characteristics were calculated for MABC-2 and VABS-2 scores and Spearman’s rank order correlation analyses were used to examine the relationship between motor coordination and adaptive behavior. Results On average, the participants (n=26) exhibited significant challenges in regard to their motor coordination with all but two participants classified as having significant motor impairments by scoring at or below the 16th percentile on the MABC-2. Results from the correlation analyses indicated that manual dexterity was positively related to daily living skills (ρ=.58, p<.003), and overall motor coordination was positively related to daily living skills (ρ=.60, p<.003) and overall adaptive behavior (ρ=.57, p<.003). In all instances, better motor coordination was related to more adaptive behaviors. Conclusion These results highlight the profound motor coordination challenges that children with ASD experience and also suggest that these challenges, particularly with manual dexterity, are related to the daily behavior of children with ASD. The interrelatedness of motor and adaptive behavior suggests the need to further explore the impact of motor-based interventions for this population, as well as conduct longitudinal studies to disentangle these relationships.